IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 7 TAHUN 2021 TERHADAP KEMUDAHAN PERIZINAN BERUSAHA BERBASIS RISIKO UMKM DI KABUPATEN OGAN KOMERING ILIR - Azizah, Azizah; Sari, Yessy Meryantika; Karyadin, Karyadin; Sari, Dwi Purnama (Solusi, 2025)
This research aims to evaluate the effectiveness of Government Regulation Number 7 of 2021 in facilitating ease of risk-based business licensing for Micro, Small and Medium Enterprises (MSMEs), as well as to understand its impact on the smooth running of MSME business activities. The research method used is empirical research, namely collecting data directly from the field to obtain information from primary sources which is then analyzed in depth to obtain accurate conclusions. This research is descriptive in nature, and the data used consists of primary and secondary data. The research results show that the implementation of PP No. 7 of 2021 has been implemented by the Office of Cooperatives, SMEs and Industry, Ogan Komering Ilir Regency. Based on this regulation, the agency assists MSMEs in obtaining Business Identification Numbers (NIB) through the OSS (Online Single Submission) system in accordance with applicable legal provisions. However, there are still many MSME players who do not have business permits because of the lack of information or public knowledge regarding business permits, so they have not yet taken care of the NIB and having a business permit for MSMEs has a positive impact from an economic perspective, such as increasing income, business legality, ease of obtaining capital, access to assistance, as well as the opportunity to receive empowerment assistance from the government.